2021
DOI: 10.21468/scipostphys.10.3.057
|View full text |Cite
|
Sign up to set email alerts
|

Spin-polarized two-dimensional electron/hole gases on LiCoO$_2$ layers.

Abstract: First-principles calculations show the formation of a 2D spin polarized electron (hole) gas on the Li (CoO_22) terminated surfaces of finite slabs down to a monolayer, in remarkable contrast with the bulk band structure, which is stabilized by Li donating its electron to the CoO_22 layer forming a Co-d-t_{2g}^6d−t2g6 insulator. By mapping the first-principles computational results to a minimal tight-binding models corresponding to a non-chiral 3D generalization of the quadripartite Su-Schrieffer-Heeger (SSH4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The consequence of a terminal lithium layer was the subject of discussion in Sec. VII B and [141] where a 2DEG was predicted to exist above the surface of the flake. We offer the speculation that if the electron gas were indeed present, it would certainly pose a large energy barrier needing to be overcome for hole-conduction between LCO and the contacting metal to take place, which could explain qualitatively the Schottky barrier behavior observed here.…”
Section: Transport In 2d Licoo2 Nanosystemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consequence of a terminal lithium layer was the subject of discussion in Sec. VII B and [141] where a 2DEG was predicted to exist above the surface of the flake. We offer the speculation that if the electron gas were indeed present, it would certainly pose a large energy barrier needing to be overcome for hole-conduction between LCO and the contacting metal to take place, which could explain qualitatively the Schottky barrier behavior observed here.…”
Section: Transport In 2d Licoo2 Nanosystemsmentioning
confidence: 99%
“…We discovered these effects somewhat serendipitously by performing DFT calculations for a monolayer of LiCoO 2 , inspired by the exfoliation experiments. [141] In other words, we considered a monolayer of CoO 2 consisting of the same connected CoO 6 octahedra as in the R 3m structure and with Li attached to one side. Intriguingly what we found was that the Li-sp z orbital related bands, which in bulk occur at high energy above the Fermi level, came down in energy and near Γ formed an occupied pocket below the Fermi level, which mani-fests itself in the formation of a two-dimensional electron gas (2DEG) with an increased electron density on the Li and floating above it, extending into the vacuum region.…”
Section: B Topological Surface States In Licoo2mentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that the electronic properties of the surface are heterogeneous, dependent on the spatial concentration of lithium, where any unideal ordering ( x ≠ 0.5) may induce Anderson localization effects and inhibit conduction. Additionally, it has been recently suggested that these insulating surfaces are likely due to a spin-polarized 2D electron gas of topological origin, which occurs for the lithium-terminated single crystals of Li x CoO 2 . Briefly, in this report, Kumar et al investigate the nature of polar surfaces of Li x CoO 2 in the 2D limit, modeling the formation of electron or hole-gas surface states when thin flakes are terminated by lithium or CoO 2 layers, respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It follows that the ability to investigate a material in the 2D limit becomes advantageous, where correlated effects are more easily observed and modified. Additionally, the reduced dimensionality can produce quantum effects not typically observed in the bulk, such as insulating polar surfaces and topological surface states . However, due to the challenges of electrostatic stabilization between layers, studies of these states in layered cobalt oxides are limited.…”
Section: Introductionmentioning
confidence: 99%